In vitro and in vivo effects of doxycycline on Toxoplasma gondii. - Chang, H R (1990)
We investigated the effects of doxycycline on Toxoplasma gondii infections in vitro and in vivo. Resident peritoneal macrophages were infected with the virulent RH strain of T. gondii and exposed to doxycycline at different concentrations. The antitoxoplasmic activity of doxycycline was first assessed with [3H]uracil, which is incorporated by the parasite but not the host cell. The concentration of doxycycline that inhibited 50% of the radioactive uptake was calculated to be 6.4 micrograms/ml (95% confidence limits, 5.07 to 8.06 micrograms/ml); the concentration of doxycycline that inhibited 90% of the radioactive uptake was 14 micrograms/ml. Tetracycline was ineffective up to 40 micrograms/ml. Furthermore, microscopic examination of the infected macrophages after treatment with doxycycline confirmed the inhibition of intracellular growth of T. gondii. Mice acutely infected by the intraperitoneal route with 5 x 10(3) tachyzoites of T. gondii were protected against death with a dose of 300 mg of doxycycline per kg (body weight) administered by the oral route for 10 days, starting 24 h after challenge. When mice were infected with 10(5) tachyzoites of T. gondii and treated 12 days starting 2 h after challenge, the protection and the cure rates were, respectively, 100 and 0% after doxycycline alone (300 mg/kg per day), 0 and 0% after pyrimethamine alone (12.5 mg/kg per day), and 100 and 60% after the combination of these two drugs at the same dosages given above. These results suggest that doxycycline may prove to be useful in the treatment of toxoplasmic infections.